Whose Archive?: Questions of Access to information and Memory in Rainbows End by vernor vinge. Issue 3 (January 2016) - Kozioł, Sławomir
Abstract : The article explores the issue of access to digitized archives as represented in Vernor Vinge's novel Rainbows End . After focusing on the way in which Vinge shows the consequences of digitization of institutional archives, including their greater transparency but also methods of thwarting searches in them, the analysis moves on to investigate the novel's treatment of the problem of access to personal data, exploring questions of security and surveillance, as well as the changing relationship between personal and collective memory. Finally, the article focuses on the way in which Vinge shows how easier access to digital archives may influence human creativity. His vision of the future of archives is described in the context of current theoretical discussions concerned with the general idea of the archive, and with the fate of archives in the digital era.